2014
DOI: 10.5539/sar.v3n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Drought and Wounding Stress on Soluble Phenols and Proteins in Potato Tubers

Abstract: Potato is a valuable source for phytochemicals like vitamins, minerals, plant phenols, amino acids and proteins. However, environmental stress may affect the level of all these components. In this study, two purple breeding clones and one yellow fleshed cultivar (cv.) were assessed in their response to drought and wounding stress in two consecutive years. The plants were grown in the greenhouse under control (sufficient water supply) and with drought stress conditions. After harvest the tubers were analyzed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 68 publications
2
15
1
Order By: Relevance
“…The results of this study revealed significantly higher LAH activities in drought stressed tubers than in the control tubers (Table 3A). An increase in LAH by DS was consistently found with all GTs, in the first (+42.8%) and second year (+54.7%), which supports the results of previous experiments [32].…”
Section: Protein Myo-inositol and Fatty Acidssupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study revealed significantly higher LAH activities in drought stressed tubers than in the control tubers (Table 3A). An increase in LAH by DS was consistently found with all GTs, in the first (+42.8%) and second year (+54.7%), which supports the results of previous experiments [32].…”
Section: Protein Myo-inositol and Fatty Acidssupporting
confidence: 91%
“…The analytical block digestion system Kjeldatherm®, the distillation system VAPODEST® both from C. Gerhard, Germany and the TitroLine easy apparatus from Schott Instruments, Germany were combined for the determination of crude protein by means of the Kjeldahl method [30]. Lipid acyl hydrolase (LAH) enzyme activity was measured on a UV spectrophotometer from Kontron Instruments, Germany according to Bohac [31] with modifications [32]. Extraction of total tuber lipids was performed as detailed by Bligh and Dyer [33] before fatty acids were analyzed as fatty acid methyl ester (FAME) on an Agilent 6890A GC with FID (Agilent Technologies, USA) as described by Arens et al [34].…”
Section: Analysesmentioning
confidence: 99%
“…Analyses: Lyophilized tissue samples were used for the analyses of anthocyanins according to Fuleci and Francis [16] and for the assay of LAH activity according to Bohac [5], both with modifications [17]. Total amounts of Ac were measured at 545 nm on a UV spectrometer (Kontron Instruments, Germany), then calculated as malvidin-3-p-coumaryl-glucoside and expressed as milligrams per 100 grams freeze-dried matter (FDM).…”
Section: Drought Stressmentioning
confidence: 99%
“…Amounts of proteins were expressed as mg/mL of tissue extract. Total amounts of free AAS were measured by the method of Cohen & Michaud [21] adapted to a Luna C18 (2) bonded silica column (Phenomenex, Germany) according to Hernández-Orte et al [22] with modifications [17]. The HPLC assay was carried out on an Agilent 1100 series liquid chromatograph system (Agilent Technologies, Germany), and amounts of AAS were expressed in milligrams per 100 g of FW.…”
Section: Drought Stressmentioning
confidence: 99%
“…SP Mafakheri et al, 2011), Chl (Ma et al, 2004;Zaefyzadeh et al, 2009), RWC (Golparvar, 2012;Teulat et al, 2003), RWL (Zhang et al, 2004), MDA (Guan et al, 2015), SOD and POD activities (Yang et al, 2014;Weng et al, 2015) which are closely associated with drought tolerance can be used as reference indexes for evaluation of drought resistance among varieties. And these indexes have been widely utilized for the study of maize, potato, soybean and wheat drought resistance (Bano et al, 2012;Mohammadkhani and Heidari, 2008;Paknejad et al, 2007;Wegener, et al, 2014;Zhang et al, 2007b).…”
Section: Changes In Physiological Indexes In Response To Drought Stressmentioning
confidence: 99%